Hepatitis B infection in patients attended at sexually transmitted disease Clinic from Federal Fluminense University - Oliveira, Ledy H.S.; Silva, Isabel R.; Almeida, Nubia K.; Xavier, Bruno R.S.; Cavalcanti, Silvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Background: The relevance of sexual transmission on Hepatitis B epidemiology. Objectives: The aim of this paper is to determine the prevalence and risk factors for HBV infection in patients at-tended at DST clinic from UFF. Methods: ln aretrospective study seroprevalence of hepatitis B virus (HBV) was investigate in 440 patients attended at DST /UFF clinic over an 11 month period in 1997. Serum of each patient was assayed for anti-HBc marker. Demographic and risk factor data and his-tory of hepatitis were extracted from clinic notes. Results: Seroprevalence to anti-HBc, was 13% . Variables associated risk factors (lifestyle, anal cour-se, blood transfusion, drug injecting or not, syphilis s eropositivity, history ofhepatitis, multiple partners, current or past clinic history of STD, partner with STD), and variables not associated with risk factors (sex, age, marriage, education, and socioeconomic conditions) were included in a statistic analysis. A significant association among homo/bisexual behaviour, anal course and blood transfusion was done. HIV infection and drug abuse (injecting or not) also had implication in HBV infection. Conclusions: Although HBV prevalence found in this sample according to the prevalence in areas of the intermediate endemicity, we should attempt to the potential virus pathogenesis. Considering that vaccine policies don’t include adult people with risk lifestyle for HBV infection, we suggest that the patients attending in SDT clinics should be tested for HBV and seronegative should be advised to be immunised against HBV.